2014
DOI: 10.1086/675683
|View full text |Cite
|
Sign up to set email alerts
|

Integrating intermittent streams into watershed assessments: applicability of an index of biotic integrity

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 37 publications
(28 reference statements)
1
34
0
1
Order By: Relevance
“…Therefore, we have scant information about their spatial extent (Meyer and Wallace, 2001;Benstead and Leigh, 2012;Datry et al, 2014a), hydrological regime Datry et al, 2014a) and, as they have been excluded from bioassessment programs (e.g., Hall et al, 1998;Peck et al, 2006;, and about their ecology (Williams, 2008;Larned et al, 2010;Datry et al, 2014a). Thus, as stated in Mazor et al (2014), "many surveys of ambient stream conditions are incomplete, biomonitoring programs do not provide comprehensive evaluations of stream health or complete assessments of watershed or regional conditions, and watershed-management and resource-protection programs based on these assessments might be compromised".…”
Section: An Update Of Research On Eu-med Nprsmentioning
confidence: 99%
“…Therefore, we have scant information about their spatial extent (Meyer and Wallace, 2001;Benstead and Leigh, 2012;Datry et al, 2014a), hydrological regime Datry et al, 2014a) and, as they have been excluded from bioassessment programs (e.g., Hall et al, 1998;Peck et al, 2006;, and about their ecology (Williams, 2008;Larned et al, 2010;Datry et al, 2014a). Thus, as stated in Mazor et al (2014), "many surveys of ambient stream conditions are incomplete, biomonitoring programs do not provide comprehensive evaluations of stream health or complete assessments of watershed or regional conditions, and watershed-management and resource-protection programs based on these assessments might be compromised".…”
Section: An Update Of Research On Eu-med Nprsmentioning
confidence: 99%
“…Nevertheless, variability was the highest for non-perennial streams examined, similar to results from California. Even with the above-described limitations and deficiencies, the development of methods for adapting traditional biomonitoring tools to Mediterranean streams and rivers is underway [117,118]. For example, in California, Mazor et al [118] demonstrated acceptable performance of current biomonitoring indices such as the Southern California Index of Biotic Integrity (IBI) for many intermittent streams.…”
Section: Biomonitoring In Highly Variable Systemsmentioning
confidence: 99%
“…Even with the above-described limitations and deficiencies, the development of methods for adapting traditional biomonitoring tools to Mediterranean streams and rivers is underway [117,118]. For example, in California, Mazor et al [118] demonstrated acceptable performance of current biomonitoring indices such as the Southern California Index of Biotic Integrity (IBI) for many intermittent streams. Moreover, innovative approaches, such as one based on terrestrial fauna [119,120] are being developed.…”
Section: Biomonitoring In Highly Variable Systemsmentioning
confidence: 99%
“…In addition, this work could be relevant for watershed management. The knowledge of the duration and the variability of the drying phase is very important for assessing the ecological status of IRES (Mazor, Stein, Ode, & Schiff, ; Prat et al, ). It could also help to identify which metrics are the most relevant for detecting human impacts (Datry, Bonada, & Boulton, ).…”
Section: Resultsmentioning
confidence: 99%